2014
DOI: 10.3389/fnagi.2014.00217
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of central nervous system resources for preparation and performance of complex walking tasks in older adults

Abstract: Introduction: Walking in the home and community often involves performance of complex walking tasks. Understanding the control of such tasks is crucial to preserving independence and quality of life in older adults. However, very little research has been conducted in this area. Here, we assess the extent to which two measures of central nervous system (CNS) activity are responsive to the challenges posed by preparation and performance of complex walking tasks. Prefrontal cortical activity was measured by funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
107
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 48 publications
12
107
0
1
Order By: Relevance
“…Piper band activity in the cortex has been attributed to interactions among cortical regions that are involved in movement execution under variable conditions that require attentional resources, such as to integrate visual and somatosensory information [Brown, 2000, Omlor, Patino, 2007]. This is generally consistent with the prior finding that walking adaptability tasks invoke increased cortical activity in regions important to attention and motor planning [Clark, 2015, Clark et al, 2014]. Furthermore, prior work has shown that EMG synchrony in the Piper range exhibits task-dependent changes that are consistent with the attentional and physical demands of various walking adaptability tasks [Clark, Kautz, 2013].…”
Section: Introductionsupporting
confidence: 72%
“…Piper band activity in the cortex has been attributed to interactions among cortical regions that are involved in movement execution under variable conditions that require attentional resources, such as to integrate visual and somatosensory information [Brown, 2000, Omlor, Patino, 2007]. This is generally consistent with the prior finding that walking adaptability tasks invoke increased cortical activity in regions important to attention and motor planning [Clark, 2015, Clark et al, 2014]. Furthermore, prior work has shown that EMG synchrony in the Piper range exhibits task-dependent changes that are consistent with the attentional and physical demands of various walking adaptability tasks [Clark, Kautz, 2013].…”
Section: Introductionsupporting
confidence: 72%
“…These findings add to other potential benefits of using adaptability tasks in rehabilitation, including more effective engagement of cerebral circuits of locomotor control 9,10 and high functional importance of adaptability tasks 4 .…”
Section: Resultsmentioning
confidence: 62%
“…Alternatively, the increased utilization of cognitive resources, operationalized using PFC HbO 2 levels, among individuals with slow gait may have contributed to their reduced gait speed costs compared to participants with normal gait. An additional study found that PFC activity was elevated during complex walking tasks relative to a control task, which the authors posited to reflect preserved quality of gait during obstacle negotiation tasks (26). …”
Section: Discussionmentioning
confidence: 99%